Occlusion dysfunction and Alzheimer’s disease: Mendelian randomization study - Wang, Qing; Zhen, Wenyu; Hu, Rui; Wang, Zifei; Sun, Yuqiang; Sun, Wansu; Huang, Chunxia; Xu, Jianguang; Zhang, Hengguo (Frontiers in Aging Neuroscience, 2024)
Aim: Occlusion dysfunction (OD) is increasingly linked to Alzheimer's disease (AD).This study aimed to elucidate the causal relationship between OD and AD using mendelian randomization (MR) analysis.Genome-wide association study (GWAS) meta-analysis data obtained from FinnGen, IEU Open GWAS, and UK Biobank (UKBB) was represented as instrumental variables. We validated the causal relationship between periodontal disease (PD), loose teeth (PD & occlusion dysfunction), dentures restoration (occlusion recovery), and AD.Results: According to the MR analysis, PD and AD have no direct causal relationship (P = 0.395, IVW). However, loose teeth significantly increased the risk of AD progression (P = 0.017, IVW, OR = 187.3567, 95%CI = 2.54E+00 -1.38E+04). These findings were further supported by the negative causal relationship between dentures restoration and AD (P = 0.015, IVW, OR = 0.0234, 95%CI = 1.13E-03 -0.485).The occlusion dysfunction can ultimately induce Alzheimer's disease.Occlusion function was a potentially protective factor for maintaining neurological health.